Development of an Immunohistochemical Assay to Detect the Ataxia-Telangiectasia Mutated (ATM) Protein in Gastric Carcinoma. Issue 4 (April 2020) - Miller, Rachel M.; Nworu, Chinedu; McKee, Laurel; Balcerzak, Denis; Pham, Linh; Pugh, Judith; Liu, Yu-Zhen; Gustafson, Heather; Marwah, Ekta; Lamb, Tiffany; Clements, June
Abstract : Ataxia-telangiectasia mutated (ATM), a key activator of DNA damage response mechanisms, represents a potential biomarker for targeted gastric carcinoma therapies. A phase II study (Study 39; NCT01063517) designed to investigate the combination olaparib plus paclitaxel in patients with recurrent or metastatic gastric cancer did not meet its primary endpoint of progression-free survival; however, an improvement in the secondary endpoint of overall survival was recorded with a greater overall survival benefit noted in patients with ATM-negative tumors. An ATM immunohistochemical (IHC) diagnostic assay was developed to identify patients who may respond favorably to targeted therapies and deployed in the confirmatory phase III GOLD trial (NCT01924533). The VENTANA ATM (Y170) assay was developed for investigational use in formalin-fixed, paraffin-embedded gastric carcinoma samples using an anti-ATM rabbit monoclonal antibody (clone Y170) and was optimized with OptiView DAB IHC Detection Kit on a BenchMark ULTRA instrument. The assay was deployed in studies assessing sensitivity, specificity, robustness, precision, and determining optimal ATM staining cutoff to define ATM-deficiency (ATM-low). The ATM (Y170) assay met all predefined product development acceptance criteria. Multiple parameters were characterized, including repeatability, reproducibility, analytical sensitivity, specificity, robustness, and product stability. The scoring algorithm was defined; gastric carcinoma samples were considered ATM-negative or ATM-positive when <25% or ≥25%, respectively, of tumor cell nuclei expressed ATM at any IHC stain intensity and nuclei of immune and/or endothelial cells expressed ATM at a moderate stain intensity (internal positive control). Results highlight reproducibility of the assay, supporting suitability for investigational use for evaluation of gastric carcinoma samples using tumor cell staining cutoff of <25% to define ATM-deficiency. Using this ATM assay, phase III GOLD trial (NCT01924533) clinical trial did not meet its primary endpoint, only suggesting, but not demonstrating, that assessment of ATM levels by IHC could possibly be useful in assessing the degree of benefit that may be achieved by adding olaparib to paxitaxel when treating gastric carcinoma. The utility of ATM (Y170) assay as a companion diagnostic requires further clinical validation. Abstract : Supplemental Digital Content is available in the text.